The role of international accreditation agencies in business school practices’ institutionalization processes - Kit, Anaïs (Management international / International Management / Gestiòn Internacional, 2024)
This paper examines the mechanisms underlying the institutionalization process of soft-regulations in the field of business schools, where international accreditation agencies are perceived as dictating the standards. The study examines the discursive and monitoring mechanisms used by the EFMD to promote EQUIS accreditation since its creation. Combining a critical discourse analysis of accreditation guidebooks and interviews with EQUIS regulators, our findings illustrate and build on the institutionalization curve proposed by Lawrence et al. (2001). Contributing to research about the convergence of business schools’ practices, we offer a perspective into the characteristics of institutional actors’ legitimacy strategies underpinning the institutionalization process.